A Critical Review of Cannabis, its Toxicity and Management - vishnoi, Rinkesh; Sharma, Anita; Pandey, Chandra dev (International Research Journal of Ayurveda & Yoga, 2024)
Cannabis is a cannabinaceae family herb which is known as bhang is flowering plant. It is neurotoxic cerebral deliriants poisons deliriant means delirium induce referring to hallucinogen property. For ages, the cannabis plant, native to Central Asia and the Indian subcontinent, has been utilised as a recreational and entheogenic drug, as well as in a variety of traditional medicines. This herb is grown as an agriculture crop for the purpose of pharmaceutical to formation of many type medicine to treat pain and induce sleep. Many people take long period of cannabis produce many side effect like irritability, agitation, insomnia, drugs craving, depression, tremors, nausea, sweating and body ache. Charas, ganja, majun, hashish, hash oil, and sinsemilla are the substance of cannabis. Cannabis also known as the Indian hemp and qinnab.